Implementation Of Risk Management In The Traditional Shopping Center Of Jetak Village For Fire Prevention - Novi Styaningsih; Arina Nuraliza Romas (J-MARK (Jurnal Manajemen Risiko dan Keuangan), 2023)
There were 17,768 cases of fires in Indonesia in 2021, with 5,274 cases of which were caused by short-circuit electricity. In early January 2022 there was a case of fire that occurred in the largest traditional shopping center in Kudus caused by a circuit of currents. The purpose of this study is to identify risks, compile risk ratings, and control strategies carried out in minimizing fire risk. Methods of retrieving data with observation and interviews using hazard identification and risk assessment checklist sheets. While the assessment method uses a risk assessment matrix. The results of observation obtained the source of danger comes from the condition of the building facilities and the process of activities carried out. While the results of the classification of risks obtained nine risks that can be the cause of fire in the traditional shopping center of Jetak Village and divided into 3 levels, namely very high risk level, high risk and moderate risk. Dominant risks that can occur such as short circuit of electric current due to cable use, cable conditions, placement of electrical panels in dangerous locations and excessive use of outlets. Mitigation measures that can be used are risk reduction by moving panel locations, using standard cables, applying the 5R rule and providing signs of danger at the source of existing hazards. From these results, efforts are needed to prevent and fire management, namely the provision of building safety facilities such as evacuation routes, gathering points and the provision of Light Fire Extinguishers.